HUBUNGAN PENGETAHUAN AYAH TENTANG PENGASUHAN DENGAN PERAN AYAH DALAM PENGASUHAN ANAK DI TK AISYIYAH DESA PENYASAWAN KECAMATAN KAMPAR - Sari, Indah Azma; Zulkifli N, Zulkifli N; Hukmi, Hukmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrack: The aim of this research is to know whether there is any correlation between of father's knowledge about parenting with the role of father in parenting in Aisyiyah Kindergarten, Penyasawan village, District of Kampar. The population in this study are all fathers who have children in Aisyiyah kindergarten, Penyasawan village, District of Kampar that consists of 89 person, the samples of this research are 89 person. Method of this research is quantitative correlation to know the correation between independent variable and dependent variable. The technique of collecting data used tests and quistioner in Likert scale form. The technique of analyzing data used scale test and statistic analitical by using SPSS program for Windows Ver.17. Based on hypothesis test results there is a significant positive correlation between the father's knowledge about parenting with the role of father in parenting in Aisyiyah Kindergarten, Penyasawan village, District of Kampar. It can be known from the value of correlation coefficient of rxy = 0.656 and significant level is 0,000 <0.05. The correlation between father’s knowledge about parenting with the role of father in parenting is in the high level which is the KP = r² x 100% = 43%, it means that father’s knowledge about parenting affect the role of father in parenting as much as 43%.Key Words: Father’s Knowledge About Parenting, The Role Of Father In Parenting